Students' Perceptions of the Effectiveness of Using Non-Traditional Techniques to Improve Oral Communication Skills - Dr.Khaled A.Dweikat; Dr.Fayez T. Aqel (My University, 2012)
Speaking is considered a major skill of any language. Some linguists, in this regard, define language as nothing but a system of vocal symbols used to communicate ideas and thoughts among the members of a certain social society. This shows that language is mainly an oral activity and writing is considered a secondary system derived form the spoken language. As a result, students who learn English either as a foreign or a second language should be encouraged to speak the language to a certain extent that enables them to communicate with other speakers of the language. To produce students who are proficient in a foreign language, educators should ensure that their students are participating in a variety of performance-based tasks based upon authentic use of language for communication (Fuller, 2011). Foreign language teachers, then, should design assessment practices using a variety of communicative contexts, thus providing a way to document students’ progress in language ability as they continue in a foreign language program of study. Moreover, students who study English either as a foreign language or a second language are assumed to be provided with more and more opportunities to practice oral communication skills inside and outside the classroom in natural and meaningful situations. This can be done by using different types of activities and practices that motivate the students to use the language naturally and purposefully in meaningful situations. Contextualization of language, in this regard, has been shown to increase students’ motivation, engagement in learning, the amount of information learned, and their self-perception of competence in the target language (Cordova & Lepper, 1996). Based on this assumption, students' perspectives should be investigated and taken into account when they are involved in the teaching –learning process especially at higher education levels as they represent the first beneficiaries of the teaching-learning process. Moreover, university students are to be given more chances to actively participate in selecting some teaching materials which are hoped to suit their needs and interests especially when talking about learning languages and English in particular. Undoubtedly, students nowadays seem to be mature enough and more self –confident to give their own opinions as they are open to various types of technological advancements including computers, the Internet, social networks, YouTubes, up-to-date mobiles, high-technology ….etc.
Students who are registered in the so-called Oral Communication Course were involved in various types of activities, such as presentations, games, YouTube materials, acting, puzzles, poetry recitation, summaries, jokes, dramatization, improvisation, PowerPoint presentations and so on. Oral Communication course plan includes different forms of evaluation procedures such as writing exams based on language use activities and situations, in-class participation and oral presentations, oral exam, on-going assessment, fluency-based observation and so on.

Speaking is considered a major skill of any language. Some linguists, in this regard, define language as nothing but a system of vocal symbols used to communicate ideas and thoughts among the members of a certain social society. This shows that language is mainly an oral activity and writing is considered a secondary system derived form the spoken language. As a result, students who learn English either as a foreign or a second language should be encouraged to speak the language to a certain extent that enables them to communicate with other speakers of the language. To produce students who are proficient in a foreign language, educators should ensure that their students are participating in a variety of performance-based tasks based upon authentic use of language for communication (Fuller, 2011). Foreign language teachers, then, should design assessment practices using a variety of communicative contexts, thus providing a way to document students’ progress in language ability as they continue in a foreign language program of study. Moreover, students who study English either as a foreign language or a second language are assumed to be provided with more and more opportunities to practice oral communication skills inside and outside the classroom in natural and meaningful situations. This can be done by using different types of activities and practices that motivate the students to use the language naturally and purposefully in meaningful situations. Contextualization of language, in this regard, has been shown to increase students’ motivation, engagement in learning, the amount of information learned, and their self-perception of competence in the target language (Cordova & Lepper, 1996). Based on this assumption, students' perspectives should be investigated and taken into account when they are involved in the teaching –learning process especially at higher education levels as they represent the first beneficiaries of the teaching-learning process. Moreover, university students are to be given more chances to actively participate in selecting some teaching materials which are hoped to suit their needs and interests especially when talking about learning languages and English in particular. Undoubtedly, students nowadays seem to be mature enough and more self –confident to give their own opinions as they are open to various types of technological advancements including computers, the Internet, social networks, YouTubes, up-to-date mobiles, high-technology ….etc.
Students who are registered in the so-called Oral Communication Course were involved in various types of activities, such as presentations, games, YouTube materials, acting, puzzles, poetry recitation, summaries, jokes, dramatization, improvisation, PowerPoint presentations and so on. Oral Communication course plan includes different forms of evaluation procedures such as writing exams based on language use activities and situations, in-class participation and oral presentations, oral exam, on-going assessment, fluency-based observation and so on.
Students' Perceptions of the Effectiveness of Using Non-Traditional Techniques to Improve Oral Communication Skills